Cost of Price Stabilization Policies in a Strongly Inflationary Economy - Selowsky, Marcelo (Quarterly Journal of Economics, 1973)
I. A short-run model of inflation and output, 45. — II. Empirical evaluation, 53. — III. Discussion of the results, 54. — Appendix: Some of the implicit assumptions of the model, 58.